SOCIALPSYKOLOGISKE REFLEKSIONER OVER ET REGELRANDZONEFELT - Nielsen, Anne Maj; Mathiassen, Charlotte (Psyke & Logos, 2015)
Crime, resocialization and totalinstitutions define three research fields. Some discourses about social integration common to these research fields also constitute the field of social psychology. These discourses are presented and discussed in the article. Based on the discussion, a common field of research is outlined. This common field is the study of zones of contrasting laws, rules and/or codes of conduct in marginal positions, where participants are in transition from one community to another, and needs to negotiate and/or change motives, intentions, values and attitudes in order to behave according to the laws/ rules/codes of conduct in the future community (for example, a prison can be the future community for the sentenced time). This research field is labeled zones of contrasting margins. Some of the challenges that may rise due to the outlined characteristics of zones of contrasting margins are discussed. Finally, some questions are posed considering the implications of this approach to future research in the field.